The Ess1 prolyl isomerase: Traffic cop of the RNA polymerase II transcription - Hanes, Steven D. (2014)
Ess1 is a prolyl isomerase that regulates the structure and function of eukaryotic RNA polymerase II. Ess1 works by catalyzing the cis/trans conversion of pSer5–Pro6 bonds, and to a lesser extent pSer2–Pro3 bonds, within the carboxy-terminal domain (CTD) of Rpb1, the largest subunit of RNA pol II. Ess1 is conserved in organisms ranging from yeast to humans. In budding yeast, Ess1 is essential for growth and is required for efficient transcription initiation and termination, RNA processing, and suppression of cryptic transcription. In mammals, Ess1 (called Pin1) functions in a variety of pathways, including transcription, but it is not essential. Recent work has shown that Ess1 coordinates the binding and release of CTD-binding proteins that function as co-factors in the RNA pol II complex. In this way, Ess1 plays an integral role in writing (and reading) the so-called CTD code to promote production of mature RNA pol II transcripts including non-coding RNAs and mRNAs.